Cyclosporin A Promotes in vivo Myogenic Response in Collagen VI-Deficient Myopathic Mice - Gattazzo, Francesca; Molon, Sibilla; Morbidoni, Valeria; Braghetta, Paola; Blaauw, Bert; Urciuolo, Anna; Bonaldo, Paolo (Frontiers in Aging Neuroscience, 2014)
Mutations of genes encoding for collagen VI cause various muscle diseases in humans, including Bethlem myopathy and Ullrich congenital muscular dystrophy. Collagen VI null (Col6a1–/–) mice are affected by a myopathic phenotype with mitochondrial dysfunction, spontaneous apoptosis of muscle fibers and defective autophagy. Moreover, Col6a1–/– mice display impaired muscle regeneration and defective self-renewal of satellite cells after injury. Treatment with cyclosporin A (CsA) is effective in normalizing the mitochondrial, apoptotic and autophagic defects of myofibers in Col6a1–/– mice. A pilot clinical trial with CsA in Ullrich patients suggested that CsA may increase the number of regenerating myofibers. Here we report the effects of CsA administration at 5 mg/kg body weight every 12 hr in Col6a1–/– mice on muscle regeneration under physiological conditions and after cardiotoxin (CdTx)-induced muscle injury. Our findings indicate that CsA influences satellite cell activity and triggers the formation of regenerating fibers in Col6a1–/– mice. Data obtained on injured muscles show that under appropriate administration regimens CsA is able to stimulate myogenesis in Col6a1–/– mice by significantly increasing the number of myogenin (MyoG)-positive cells and of regenerating myofibers at the early stages of muscle regeneration. CsA is also able to ameliorate muscle regeneration of Col6a1–/– mice subjected to multiple CdTx injuries, with a concurrent maintenance of the satellite cell pool. Our data show that CsA is beneficial for muscle regeneration in Col6a1–/– mice.